Advanced applications of motion analysis in sports biomechanics - Ferdinands, R. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Motion analysis is utilized to capture various raw linear positional data of markers placed on a body performing a movement sequence in sport. The application of motion analysis involves biomechanical modeling to calculate various kinematic and kinetic derived variables to understand the principles of motion. Since biomechanists are recruited as consultants to teams and coaches in sport teams, it is essential that they apply motion analysis to not only evaluate individual performance, but suggest methods of optimizing technique for enhanced performance and injury risk reduction. This presentation will show how advanced applications of motion analysis can lead to the biomechanical enhancement of sports performance.